Low bone density, vertebral fracture and FRAX score in kidney transplant recipients: A cross-sectional cohort study - VELİOĞLU, ARZU; YAVUZ, DİLEK; AŞICIOĞLU, EBRU; ARIKAN, İZZET HAKKI; BUĞDAYCI, ONUR; TUĞLULAR, ZÜBEYDE SERHAN (PUBLIC LIBRARY SCIENCE, 2021)
Background Kidney transplantation (KT) recipients are at increased risk of low bone density (LBD) and fractures. In this retrospective study, we investigated bone mineral density (BMD), vertebral fractures, calculated risk for major osteoporotic fractures (MOF), and hip fractures in the KT recipients. Patients-method Patients who completed at least one year after KT were included in the analysis. Demographic, clinical, and laboratory data were recorded. Measurements of BMD were performed by dual-energy X-ray absorptiometry. Vertebral fractures were assessed using semi-quantitative criteria with conventional radiography. The ten-year risk for MOF and hip fracture were calculated using the FRAX@ tool with BMD. Results One hundred fifty-three KT recipients were included in the study. The population included 77 women. The mean age at evaluation was 46,511,9 years. Seventy-eight (50.9%) patients had normal femoral neck BMD while osteoporosis and osteopenia at the femoral neck were present in 12 (7.8%) and 63 (41.1%) of the patients, respectively. Age at evaluation was the risk factor for LBD (OR 1.057; 95% CI 1.024-1.091; p = 0.001). In female KT recipients, LBD was principally affected by menopausal status whereas in males, mammalian target of rapamycin (mTOR) inhibitor use and lower BMI levels were the risk factors. The prevalent vertebral fracture was found in 43.4% of patients. In multivariate analysis, only steroid use (OR 0.121; 95% CI 0.015-0.988; p = 0.049) was found to be associated with prevalent fracture. Among all KT recipients, 1.9% had a high MOF probability (>= 20% risk of fracture), and 23.5% had high hip fracture probability (>= 3% risk of hip fracture) according to FRAX. Conclusion Exploring the prevalence of LBD and vertebral fracture and the risk factors would help clinicians to modify long-term follow-up strategies. Furthermore, the high hip fracture risk probability in our cohort suggested that there is a need for longitudinal studies to confirm the validity of the FRAX tool in the transplant population.
Keywords: MINERAL DENSITY; DISEASE; RISK; OSTEOPOROSIS; ASSOCIATION; PREVALENCE